Effect of UV-C Radiation, Ultra-Sonication Electromagnetic Field and Microwaves on Changes in Polyphenolic Compounds in Chokeberry (Aronia melanocarpa) - Cebulak, Tomasz (Molecules, 2017)
Chokeberry fruits are highly valued for their high content of polyphenolic compounds. The use of such abiotic stress factors as UV-C radiation, an electromagnetic field, microwave radiation, and ultrasound, at different operation times, caused differentiation in the contents of anthocyanins, phenolic acids, flavonols, and flavan-3-ols. Samples were analyzed for contents of polyphenolics with ultra-performance liquid chromatography and photodiode detector-quadrupole/time-of-flight mass spectrometry (UPLC-PDA-MS/MS). The analysis showed that after exposure to abiotic stress factors, the concentration of anthocyanins ranged from 3587 to 6316 mg/100 g dry matter (dm) that constituted, on average, 67.6% of all identified polyphenolic compounds. The second investigated group included phenolic acids with the contents ranging between 1480 and 2444 mg/100 g dm (26.5%); then flavonols within the range of 133 to 243 mg/100 g dm (3.7%), and finally flavan-3-ols fluctuated between 191 and 369 mg/100 g dm (2.2%). The use of abiotic stress factors such as UV-C radiation, microwaves and ultrasound field, in most cases contributed to an increase in the content of the particular polyphenolic compounds in black chokeberry. Under the influence of these factors, increases were observed: in anthocyanin content, of 22%; in phenolic acids, of 20%; in flavonols, of 43%; and in flavan-3-ols, of 30%. Only the use of the electromagnetic field caused a decrease in the content of the examined polyphenolic compounds.